(untitled) (Conferencea, 2023)
In this article, the works of Dilshod Barno and Uvaisi, patron of science and unique creative woman, contribution of science and enlightenment to the development of the state. The role of their educational, socio-philosophical views in the development of the society of their time and today is discussed.